On the determination of the shape-type of particles - Streit, Franz (Image analysis and stereology, 2008)
Based on observations on similar-looking randomly deformed particles inferenceis made about the original common shape-type of these particles by means of statistical tests.
Keywords: Particle Size; Vzorec, razpoznavanje; Pattern Recognition; Podatki, interpretacija statistična; Data Interpretation, Statistical; Delec, velikost; delci; oblika; stereologija